Developing Alternative Assessment of Mathematical Performance for Vocational Students - Ruslan Ruslan; Alimuddin Alimuddin; Nasrullah Nasrullah (INVOTEC, 2018)
This research aims to develop alternative assessment that is compatible for mathematical performance and useful to nurture competencies of vocational students. It is developmental research in which there are 3Ds stages such as define, design, and develop. By this, there are three instruments developed, namely Students Performance Test (SPT), Cognitive Affective and Performance Assessment (CAPA), and Holistic and Analytic Assessment (HAA). In order to know the affectivity, not only teachers were getting involved to contribute responds, but also students of SMK Kartika Makassar were engaged to learn and being observed during instruments trial. The result shows that SPT focuses on the ability of identification and drawing, whereas CAPA was divided into some aspects of cognitive (including recall, share exactly, identify symbol and figure accurately, construct the figure), affective (including austerity, motivation, accuracy, and discipline) and psychomotor (including speed, skills, and quality). Lastly, HAA was also constructed in terms of holistic (such as grades, description, and general criteria) and analytic (accuracy of length and angles, compliance figure, and neatness). This study brings the information that alternative assessment can be applied to support classroom assessment in which performance of students should be enhanced, especially for vocational education.